2012
DOI: 10.4161/mabs.21227
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous targeting of TNF and Ang2 with a novel bispecific antibody enhances efficacy in an in vivo model of arthritis

Abstract: Despite the clinical success of anti-tumor necrosis factor (TNF) therapies in the treatment of inflammatory conditions such as rheumatoid arthritis, Crohn disease and psoriasis, full control of the diseases only occurs in a subset of patients and there is a need for new therapeutics with improved efficacy against broader patient populations. One possible approach is to combine biological therapeutics, but both the cost of the therapeutics and the potential for additional toxicities needs to be considered. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 78 publications
(97 reference statements)
1
33
0
3
Order By: Relevance
“…41 There is a bispecific antibody simultaneously targeting TNF-a and Ang2 available, which reduced the clinical symptoms and histologic scores in a murine inflammatory arthritis model. 42 On the other hand, Ang2 overexpression specifically in endothelial cells promoted inflammation responses, such as leukocyte infiltration in multiple organs, including liver, kidney, lung, and intestine. 43 Thus, our finding of the statistical interaction between ANGPT2 and CFH suggested that genes in the angiopoietin pathway and complement cascade are interactive in the pathogenesis of nAMD and PCV.…”
Section: Discussionmentioning
confidence: 99%
“…41 There is a bispecific antibody simultaneously targeting TNF-a and Ang2 available, which reduced the clinical symptoms and histologic scores in a murine inflammatory arthritis model. 42 On the other hand, Ang2 overexpression specifically in endothelial cells promoted inflammation responses, such as leukocyte infiltration in multiple organs, including liver, kidney, lung, and intestine. 43 Thus, our finding of the statistical interaction between ANGPT2 and CFH suggested that genes in the angiopoietin pathway and complement cascade are interactive in the pathogenesis of nAMD and PCV.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the importance of angiogenesis in the etiology of CD, it could be hypothesized that a more direct inhibition of vascular proliferation together with anti-inflammatory effects of anti-TNF agents, could improve therapeutic outcomes. In accordance with this hypothesis, Kanakaraj et al showed that application of a bispecific antibody, containing an angiopoietin-2 targeting peptide genetically fused to adalimumab, the anti-TNF antibody, in transgenic mouse model of arthritis, reduced both clinical and histological scores significantly better when compared with adalimumab alone [23]. It is not possible to translate these observations directly into patients with CD; nevertheless, this approach may present a next step in therapeutic strategies of chronic inflammatory disorders in the future, after critical assessment of its safety and costs.…”
Section: Discussionmentioning
confidence: 80%
“…Small binding units (e.g., from class III) attached to an IgG (H and/or L chain) or fusions of molecules of the non-Fc class to an Fc portion to increase half-life and/or effector function Zybodies Zygenia http://www.zyngenia.com/ [49,50] Fyomer/IgGs Covagen [51] Brought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 7/6/15 11:57 AM that are more far away from naturally occurring structures or if employed building blocks are intracellularly derived. However, there does not seem to be a clear rule as even pentameric antibodies decorated with Fynomers, derived from binding domains of the intracellular Fyn kinases, have been reported to show very good serum half-life and no ADA in initial pharmacokinetic studies in monkeys [47,51].…”
Section: Iv) Combinations = 'Decorated' Antibodiesmentioning
confidence: 99%